The Treasure Chest - Hebel, Johann Peter,Hibberd, John (Libris, 1994)
Johann Peter Hebel (1760-1826) was one of the greatest story-tellers in the history of German literature. The anecdotes and curiosities collected here have endeared him to generations of readers in Germany and have won him many distinguished admirers further afield, including Tolstoy and Kafka, who habitually carried a copy of Hebel stories in his pocket and referred to one of them - 'Unexpected Reunion' - as 'the most wonderful story in the world' The philosopher Ludwig Wittgenstein recommended The Treasure Chest to his pupils when he worked as a schoolteacher, and later read from it to his friends First issued in collected form in 1811, Hebel's stories were originally published in a popular almanach he edited for a wide and unsophisticated readership. They cover a broad spectrum of human experience with heroes ranging from Napoleon and the enlightened Austrian Emperor Joseph, to common soldiers, working men and women, servants and petty criminals
Keywords: German fiction - Short stories; English fiction; German fiction; Short stories; English; Short stories; German